2009
DOI: 10.1557/mrs2009.213
|View full text |Cite
|
Sign up to set email alerts
|

Ion Dynamics at Interfaces: Nuclear Magnetic Resonance Studies

Abstract: Interface engineering and the study of diffusion and transport processes through and along interfacial regions play important roles in materials science and energy research. For the latter, nanostructured materials are increasingly considered to act as powerful electrodes and solid electrolytes in sustainable energy systems, such as Li ion batteries. This is due to reduced diffusion lengths achieved when going to the nanometer scale and the fact that nanocrystalline materials with an average particle size of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 113 publications
11
91
0
Order By: Relevance
“…For the microcrystalline -LiAlO 2 , the motional narrowing starts at 600 K. For -LiAlO 2 single crystals a similar result was presented by Indris et al [13]. In the case of nanocrystalline -LiAlO 2 , the motional narrowing starts at a lower temperature due to the comparably faster diffusion in such structures [4,20].…”
Section: Dynamics Investigationssupporting
confidence: 76%
See 1 more Smart Citation
“…For the microcrystalline -LiAlO 2 , the motional narrowing starts at 600 K. For -LiAlO 2 single crystals a similar result was presented by Indris et al [13]. In the case of nanocrystalline -LiAlO 2 , the motional narrowing starts at a lower temperature due to the comparably faster diffusion in such structures [4,20].…”
Section: Dynamics Investigationssupporting
confidence: 76%
“…Lithium compounds have been intensively studied during the last few decades (see, e.g., [1][2][3][4][5][6]). The main reason for this large interest is the attractive application possibility of these materials as ion conductors in the field of energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…We note that, in general, 1 nm is a typical thickness of grain boundary/surface shell regions in nanostructured mechanochemically prepared oxides, such as cubic spinels, [47][48][49][50] olivines, 26 perovskites, 28 as well as orthorhombic and ilmenite-type complex oxides. [51][52][53] In contrast to spinel nanooxides, whose near-surface layers are disordered due to the random distribution of cations, the canted spin arrangement (in the case of magnetic oxides), as well as deformed polyhedra, 49,50 in the case of mechanosynthesized perovskites (e.g., BiFeO 3 ) and trigonal nanocrystalline oxides (e.g., LiNbO 3 ), the surface shell regions have been found to be even amorphous. 28,53 A second learning example for homogeneous mechanochemical reactions is that of mechanically induced phase transformations in oxides.…”
Section: Internal Mechanochemical Reactions: Mechanically Induced Ordmentioning
confidence: 99%
“…[51][52][53] In contrast to spinel nanooxides, whose near-surface layers are disordered due to the random distribution of cations, the canted spin arrangement (in the case of magnetic oxides), as well as deformed polyhedra, 49,50 in the case of mechanosynthesized perovskites (e.g., BiFeO 3 ) and trigonal nanocrystalline oxides (e.g., LiNbO 3 ), the surface shell regions have been found to be even amorphous. 28,53 A second learning example for homogeneous mechanochemical reactions is that of mechanically induced phase transformations in oxides. It has been shown that the occurrence of polymorphic transformations in oxides upon high-energy ball milling, and their kinetics, depends chiefly on dynamical conditions of the milling process.…”
Section: Internal Mechanochemical Reactions: Mechanically Induced Ordmentioning
confidence: 99%
“…interface engineering. [14][15][16][17][18][19] In many cases this is done following essentially two routes, viz either by (i) varying chemical compositions of, for example, non-stoichiometric compounds or (ii) via directed modification of local microstructures in order to take advantage of, e.g., nano-size or interfacial effects while the overall chemical composition roughly remains untouched. [14][15][16][17][18][20][21][22] The playground of suitable materials being helpful in the field of interesting ion conductors might be further extended when thermodynamically metastable compounds are made available, see, e.g.…”
Section: Introductionmentioning
confidence: 99%